2017
DOI: 10.1002/ejsp.2270
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ‘nothing to hide’: When identity is key to privacy threat under surveillance

Abstract: Privacy is psychologically important, vital for democracy, and in the era of ubiquitous and mobile surveillance technology, facing increasingly complex threats and challenges. Yet surveillance is often justified under a trope that one has ‘nothing to hide’. We conducted focus groups (N = 42) on topics of surveillance and privacy and using discursive analysis, identify the ideological assumptions and the positions that people adopt to make sense of their participation in a surveillance society. We find a premis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Therefore, it should be no surprise that travelers are amenable to accepting airport security when they experience recognition during screening. In fact, this finding is akin to closed circuit television (CCTV) studies that found shared identity results in more surveillance acceptance (O’Donnell et al, 2010a, b), and a study of online surveillance that indicated participants objected when they felt surveillance misrepresented them (Stuart and Levine, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it should be no surprise that travelers are amenable to accepting airport security when they experience recognition during screening. In fact, this finding is akin to closed circuit television (CCTV) studies that found shared identity results in more surveillance acceptance (O’Donnell et al, 2010a, b), and a study of online surveillance that indicated participants objected when they felt surveillance misrepresented them (Stuart and Levine, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…This option would have the benefit of being fully scalable and possibly automatable. However, the General Data Protection Regulation (GDPR) has strong requirements on the handling of personal data (including clearly visible faces) [5,16] and citizens might feel a violation of their privacy when being surveillanced [8].…”
Section: Discussionmentioning
confidence: 99%
“…While this solution entails many upsides, e.g., scalability and automation capabilities, it needs to be in-line with the privacy regulations such as the General Data Protection Regulation (GDPR) and it needs to be understood by citizens to trust and accept the approach: The protection of personal data, e.g., video streams revealing individuals' faces, is regionally required by legal regulations, such as the GDPR in the European Union [5] 1 . As numerous studies show, people feel more insecure when their personal steps are highly traceable and they compromise on their privacy while being recorded [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A key example is the so called "privacy paradox" whereby people ostensibly claim to care about their privacy but openly share information about themselves (Norberg & Horne, 2007;Spiekermann, Grossklags, & Berendt, 2001). However, the privacy paradox can be resolved in some contexts-for example, when distinguishing between different dimensions of privacy and incorporating the psychological theory of planned behaviour (Ajzen, 1991;Dienlin & Trepte, 2015) or when linking privacy to identity consequences rather than the mere presence of surveillance (Stuart & Levine, 2017).…”
Section: Defining Privacymentioning
confidence: 99%
“…These subjects include the following: (a) security , the need for certainty, stability, and safety may compete or complement the need for privacy (Bansal, ; Dourish & Anderson, ; Solove, ), yet as far as we are aware, they have not been studied in unison and are rhetorically treated as a trade‐off; (b) surveillance studies are an interdisciplinary effort that psychologists could contribute towards (Tucker, Ellis, & Harper, ). There is a research on personality traits and employer monitoring (Sayre & Dahling, ) and on the shared identities between surveillers and the surveilled (O'Donnell, Jetten, & Ryan, , ; Stuart & Levine, ; Subašić, Reynolds, Turner, Veenstra, & Haslam, ); however, intergroup relations and resistance research in social psychology could further help situate the surveillance by studying which powerful groups are enacting their influence over less powerful groups, via surveillance, the vulnerabilities that some social groups face (Anthony et al, ; Park, ) and how this is allowed or resisted (see work on the elaborated social identity model in particular, Drury & Reicher, ; Reicher, ); (3) risk taking, control, and trust are further examples of concepts extensively studied in psychology and pertinent to privacy (notable studies combining the topics include Brandimarte, Acquisti, & Loewenstein, ; Joinson, Reips, Buchanan, & Paine Scholfield, ; Saeri, Ogilvie, La Macchia, Smith, & Louis, ; Xu, Dinev, Smith, & Hart, ). Further psychological theory that could help drive this area forward include protection motivation theory (Ardion, ; Rogers, ; Rogers & Prentice‐Dunn, ), psychological reactance theory (Brehm, ), and motivational and identity approaches to decision‐making (e.g., social identity theory; Tajfel & Turner, ).…”
Section: Expanding Beyond Privacymentioning
confidence: 99%